Broken ground - Schwab, Victoria (Spirit animals. Fall of the beasts, 2016)
"A new threat -- something ancient and evil -- faces the world of Erdas and four young heroes and their spirit animals are determined to stop it as they embark on a desperate journey that takes them deep underground and to the far corners of the world."--OCLC.